Морфометричні показники вікових груп у популяціях Cypripedium calceolus L. - Решетюк, О.В. (Видавництво Чернівецького університету, 2013)
The described features passing age stages ontogeny of Cypripedium calceolus L.: latent, seedlings, juvenile, immature, virgin, gener-ative and senile. The development of C. сalceolus populations was analyzed, composition of which is determined by clear age struc-ture of individuals that can serve as the main indicator of population status and conditions of their growth. It is proved that all age stages of C. сalceolus clearly differ in morphometric parameters of plant growth and development. It is shown that during the repro-ductive period of C. calceolus, it forms dense partial clusters – clones that can charge up to 32 shoots, among which are shoots of dif-ferent stages of development. Maximum age of C. calceolus individuals was defined in natural populations (not to exceed 24 years) in Ukraine. This proves their critical situation in the plant communities. It is shown that the most rapid extinction of populations is expressed through unfavorable conditions of growth and recreational overloads of natural landscapes. The following are the differ-ences ontogeny of C. сalceolus in nature and in culture. To determine the age structure of C. calceolus populations been proposed in-dicated clues developed by the author to estimate the age groups of plants according to their morphometric parameters.
Keywords: population, locality, ontogeny, age groups, latent, immature, virgin, generative, senile stage, protocorm